An assessment of the integration of the ancestral domain sustainable development and protection plan in the comprehensive land use plan the case of municipality of Bauko in Mountain Province - Robles, Leslie Anne D.; Magnaye, Dina C.; Regunay, Jose M.; Gamboa, Mark Anthony M. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
Some of the pressing concerns faced by the indigenous communities in the Philippines include the limited access to basic services and destruction of resources with the ancestral domain. Consequently, the Indigenous Peoples Rights Act (IPRA)specifies that the Ancestral Domain Sustainable Development and Protection Plan (ADSDPP) should be submitted to the local government unit (LGU) for adoption and inclusion in their local development plans and investment programs. This is to ensure that the welfare and interests of the indigenous peoples (IP) communities will be recognized and addressed to by the government. With this, the study aimed to provide mechanisms of incorporating IP concerns in the ADSDPP to the LGU's Comprehensive Land Use Plan (CLUP). The local development planning framework generally utilized in area planning was adopted in the study. Having the Municipality of Bauko as the study site, the extent of integration between the ADSDPP and CLUP was assessed along the four (4) components of the local planning system namely planning structure, planning process, plan content and plan implementation. The factors that facilitated or hindered the integration of the ADSDPP in the CLUP were also determined. Results of the study indicated that the ADSDPP was not fully integrated in the CLUPP due to a number of gaps identified. These included absence of IP representation in the Municipal Development Council; limited participation of IP community representatives during the preparation of the CLUP; outdated information in the ADSDPP; and absence of local ordinance that will support the implementation of the ADSDPP. In order to address the gaps and facilitate the integration of IP concerns in local plans, the study recommends ensuring membership and active involvement of the IP representatives in the LGU's planning team; provision of capacity building activities to IPO and IPMR relative to development planning; synchronization of timeframe between the ADSDPP and CLUP preparation; and enhancement of ADSDPP formulation guidelines to include land use planning and zoning.
Thesis (M.A. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Land use, Rural -- Philippines -- Bauko (Mountain Province).; Land use -- Philippines -- Bauko (Mountain Province).; Sustainable development -- Philippines -- Bauko (Mountain Province).